RANCANG BANGUN SISTEM INFORMASI PUSAT KEBUGARAN â€œNIâ€™ BAROE GYMâ€ - Risyda, Fitria; Nuryamin, Yamin (Universitas Dirgantara Marsekal Suryadarma, 2020)
AbstractThe essence ofÂ by the presence of of internet medium become factor primary as the facilities and infrastructures to give this range of information .A gymnasium ni baroe the gym need once a kind of information systems that really a good place to and gave him the testimony services both to make it easy for candidates would have no trouble a member to join obligation in registering their business . An integrated information system for a gymnasium ni baroe the gym that is to date it has not yet been computerized , because data processing in which the already exists at the time a gymnasium niÂ baroe the gym this is still done manually , starting from the registration of the data , the management of the schedule , the preparation of reports on corporate secretary ronald nangoi said , so as to allow the during the process of the transactions that take place an error occurs in recording , inaccuracy of the reports prepared by the and of the delay in the for finding data the data that are needed .In designing build the system the commissioner of central information fitness niÂ baroe the gym adopting both a method of waterfall ( rosa a.s &; m notes to be so performed .Shalahuddin , 2014 ) .sehingga the system to be employed in desa s apply it more orderly well and would result in Computer Better of systems that manual to run effectively and efficiently and information systems that now more conducive system in who passed away